Ultrasonographic Efficacy of Biologic and Targeted Synthetic Disease‐Modifying Antirheumatic Drug Therapy in Rheumatoid Arthritis From a Multicenter Rheumatoid Arthritis Ultrasound Prospective Cohort in Japan. Issue 12 (28th November 2018) - Nishino, Ayako; Kawashiri, Shin‐ya; Koga, Tomohiro; Iwamoto, Naoki; Ichinose, Kunihiro; Tamai, Mami; Nakamura, Hideki; Origuchi, Tomoki; Ueki, Yukitaka; Yoshitama, Tamami; Eiraku, Nobutaka; Matsuoka, Naoki; et al.
Abstract : Objective: To explore the variables associated with initial favorable power Doppler (PD) ultrasound (US) response induced by biologic and targeted synthetic disease‐modifying antirheumatic drugs (b/tsDMARDs) in patients with rheumatoid arthritis (RA). Methods: We have been prospectively investigating the course of active RA patients using US after the introduction of b/tsDMARDs in the Kyushu region of Japan since June 2013. A total of 150 patients have completed the first 6 months of observation at present and have been evaluated. US was assessed in 22 joints of bilateral hands using gray‐scale and PD images on a scale from 0–3. The sum of these scores was used as the indicator of US disease activity. We defined PD remission as attaining a total PD score of 0 at 6 months and investigated the associated variables by multivariate logistic regression analysis. Results: The total PD and gray‐scale scores and the clinical composite measures significantly improved at 6 months, whereas these reductions were less in bDMARD switchers as compared with bDMARD‐naive patients. Multivariate logistic regression analysis showed that short disease duration, the absence of any previous use of bDMARDs, and low total PD scores at baseline were independent predictors of PD remission at 6 months. Conclusion: This present prospective US cohort has for the first time shown the variables that are associated with initial PD response to b/tsDMARDs.